The Social Construction of Reality (1966) Revisited: Epistemology and Theorizing in the Study of Religion - Dreßler, Markus (Method & theory in the study of religion, 2019)
This paper takes the social constructivist approach, formulated by Peter Berger and Thomas Luckmann, as a starting point for an investigation into epistemology and theorizing in the contemporary study of religion. It discusses various strands of scholarship in dialogue with social constructivism and questions in particular the reductionism of radical constructivist positions. Exploring the boundaries of the classical social constructivist paradigm, the article argues that students of religion should consider the implication of social, historical, embodied and material structures in the production of knowledge about religion. For that purpose, it draws on various soft realist approaches to stress the importance of remaining attentive to positionality (reflecting on the sites from where we theorize) and contextuality (reflecting on the inter-relation of discourse and materiality) in theorizing "religion". Finally, the article suggests that soft realist positions can be integrated in a slightly broadened social constructivist framework for the study of religion.